Status of talent management practices in selected public higher learning Institutions in Malaysia - Lukman@Zawawi, Mohamad; Kamal, M.Y. (2017)
Ministry of Higher Education (MOHE) has taken an initiative to implement TM practices in public Higher Learning Institutions (HLIs). Therefore, this study was conducted to examine the status of TM practices in selected public HLIs. The quantitative method has been used to conduct this research in selected public HLIs which are Universiti Sains Malaysia (USM), Universiti Pendidikan Sultan Idris (UPSI) and Universiti Teknologi Mara (UiTM). The descriptive survey has been conducted towards 714 respondents. Further, the data collected was analyzed by using IBM Statistical Packages Social Sciences (IBM SPSS) was used to analyze information obtained. USM showed the highest level of TM practice as compared to UPSI and UiTM. This research revealed that the status of TM practices in this public HLIs is still in early stages. Therefore, the result of this research would be an eye opener to the MOHE and top management of public HLIs to do a check and balance about TM practices in order to have the better managerial system in public HLIs as a whole.